2010
DOI: 10.1002/ar.21266
|View full text |Cite
|
Sign up to set email alerts
|

Calcified cartilage shape in archosaur long bones reflects overlying joint shape in stress‐bearing elements: Implications for nonavian dinosaur locomotion

Abstract: In nonavian dinosaur long bones, the once-living chondroepiphysis (joint surface) overlay a now-fossilized calcified cartilage zone. Although the shape of this zone is used to infer nonavian dinosaur locomotion, it remains unclear how much it reflects chondroepiphysis shape. We tested the hypothesis that calcified cartilage shape reflects the overlying chondroepiphysis in extant archosaurs. Long bones with intact epiphyses from American alligators (Alligator mississippiensis), helmeted guinea fowl (Numida mele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 28 publications
(26 reference statements)
5
55
0
Order By: Relevance
“…However, the power of this study is low because of the limited sample size (N3) for the S. camelus elbow replicates. Regardless, our data provide quantitative support (in a form other than that of geometric morphometric measurements) for previous claims that the articular surfaces of fossilized archosaur bones approximate the morphology of the articular cartilage in vivo (Carpenter, 2002;Bonnan and Senter, 2007;Bonnan et al, 2010). Regardless, further quantitative study is required to determine whether the ratio of area lost is equal in both articular surfaces (Tereshchenko, 1994).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…However, the power of this study is low because of the limited sample size (N3) for the S. camelus elbow replicates. Regardless, our data provide quantitative support (in a form other than that of geometric morphometric measurements) for previous claims that the articular surfaces of fossilized archosaur bones approximate the morphology of the articular cartilage in vivo (Carpenter, 2002;Bonnan and Senter, 2007;Bonnan et al, 2010). Regardless, further quantitative study is required to determine whether the ratio of area lost is equal in both articular surfaces (Tereshchenko, 1994).…”
supporting
confidence: 71%
“…(Abel, 1925;Nicholls and Russell, 1985). A general knowledge of the effect that soft tissue has on individual joint thickness and range of motion (ROM) in archosaurs would be helpful in determining these attributes (Holliday et al, 2001), but this is rarely quantified (Bonnan et al, 2010;Dzemski and Christian, 2007). Thus, as it is difficult or impossible to gauge the effects of degraded soft tissue in fossilized taxa, it is often debated whether soft tissue restricts or increases a ROM at any particular joint in fossil archosaurs (Bennett, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For A. mississippiensis, our previous data (Hutson and Hutson, 2012) showed a decrease in elbow joint ROM from ROM4 to ROM5. As it has been demonstrated that the articular cartilaginous caps of extant archosaurs may undergo statistically significant changes in length and morphological fidelity compared with the bony articular surface beneath them (Bonnan et al, 2010;Holliday et al, 2010), this ROM loss might support the pre-existing hypothesis (Lipkin and Carpenter, 2008) that the removed articular cartilage acted to increase ROM (which indicates that the humeral versus glenoid ratios of area lost did not stay the same) (Meers, 1999), but the data were inconclusive for this transition in S. camelus. Here, for humeral flexion/extension, both observers recorded decreases in ROM after articular cartilage was removed (Fig.6).…”
Section: Interpreting the Effects Of Osteology And Soft Tissues On Humentioning
confidence: 99%
“…Such sesamoid fibrocartilage is also present in human feet, reducing stress concentrations (Shaw and Benjamin, 2007). Furthermore, recent studies of extant archosaur long bones show that these can be capped with a significant layer of cartilage, adding up to approximately 10% of total bone length in certain cases (Bonnan et al, 2010;Holliday et al, 2010). This implies that also the corresponding elements in dinosaurs probably exhibited thick layers of articular cartilage, as was previously shown in a sauropod humerus (Schwarz et al, 2007b).…”
Section: Manusmentioning
confidence: 71%
“…Taking FL without the claw imprints, h would increase to 3.6 FL. Although a large cartilage covering of the long bones as supposed by Holliday et al (2010), Schwarz et al (2007b), and Bonnan et al (2010) might increase h by up to 10%, it would still result around 3 FL. The ratio of metatarsal length to footprint length is also much lower in the 3D model than proposed by Thulborn (1990;24% in the model including claw prints, 46% in Thulborn).…”
Section: D Reconstructionmentioning
confidence: 96%